Chronicling Cultures: Long-Term Field Research in Anthropology - Kemper, Robert V.; Royce, Anya Peterson (Rowman & Littlefield Publishers, 2002)
Some field sites have hosted anthropologists for as long as half a century. Chronicling Cultures collects articles from principals of many of the longest and best-known anthropology projects from four continents—the Kung, Harvard Chiapas Project, Gwembe Valley, Tzintzuntzan, and Navajo among others. These projects have brought a new understanding of change and persistence in communities over time. They have forced researchers to develop methods of involving local communities in research, of using data over generations of scholars, and of resolving ethical issues of research versus advocacy. The projects range from individual scholars who return 'home' year after year to large-scale institutionalized projects involving many researchers and numerous studies. This volume will be an important addition to the literature on fieldwork, on the history of ethnology, and on ethnographers' role in their host cultures.